AI-based IoT device for smart nation deployment - Ong, Li Yuan (2019)
Singapore being a small and densely populated city, noise pollution is everywhere, even during the quiet of the night can produce more than 55 decibels of ambient noise. Each year, various government agencies received about a total of 70,000 noise complaints, with only a small percentage of complaints were able to be supported by the use of a noise meter application using mobile phone. This proved that the noise meter application was inaccurate and inefficient. A sound sensor with the ability to measure transient noise and using artificial intelligence (AI) to classify the type of sound class produced is designed by research engineers in the NTU INFITINUS lab. The noise classification results collected are sent to the cloud for records. This project will explore using the Node.js Express framework to implement a RESTful web application for users who will be able to perform configurations for the sensors deployed and stored in the AWS Cloud.